Analisis Korelasi antara Indeks Perbedaan Vegetasi Terkoreksi (NDVI) dari Citra Sentinel-2 dan Suhu Permukaan Tanah (LST) dari Citra Sentinel-3 dalam Memantau Aktivitas Erupsi Gunung Semeru pada Tahun 2021 - Yuliana Iik Iswanti Chandra; Sukir Maryanto; Adi Susilo (Postgraduate, University of Mataram, 2025)
Mount Semeru is an active volcano located on the island of Java. On December 4, 2021, Mount Semeru erupted again, resulting in damage and loss of life. Sentinel-2 satellite imagery was utilized for mapping vegetation areas, while Sentinel-3 was employed for assessing surface temperatures. The NDVI distribution related to the Semeru volcano eruption indicates that the extent of cloud cover, water, and open vegetation was consistent before, during, and after the eruption. Before the eruption, areas of very low vegetation were more prevalent than during and after. In contrast, areas of low vegetation were more common following the eruption compared to the eruption period and before it. Medium vegetation remained dominant after the eruption in comparison to the periods before and during it. In contrast, high vegetation was most abundant during the eruption and was at its lowest before the eruption occurred. The land surface temperature recorded before the eruption ranged from a minimum of 11.8 °C to a maximum of 30.12 °C. During the eruption, temperatures peaked at 42.4 °C and dropped to a low of 14.0 °C. Following the eruption, the maximum temperature recorded was 40.8 °C, with a minimum of 11.6 °C. The presence of lava flow during and after the eruption is indicated by the red circle on the land surface temperature map, and when compared to the NDVI map, the black circle shows areas where vegetation was absent due to the lava flow observed on the land surface temperature map